Effects of electron heating and surface rippling on Rayleigh–Taylor instability in radiation pressure acceleration - X. Z. Wu; Y. R. Shou; Z. B. Guo; H. G. Lu; J. X. Liu; D. Wu; Z. Gong; X. Q. Yan (Matter and Radiation at Extremes, 2023)
The acceleration of ultrathin targets driven by intense laser pulses induces Rayleigh–Taylor-like instability. Apart from laser and target configurations, we find that electron heating and surface rippling, effects inherent to the interaction process, have an important role in instability evolution and growth. By employing a simple analytical model and two-dimensional particle-in-cell simulations, we show that the onset of electron heating in the early stage of the acceleration suppresses the growth of small-scale modes, but it has little influence on the growth of large-scale modes, which thus become dominant. With the growth of surface ripples, a mechanism that can significantly influence the growth of these large-scale modes is found. The laser field modulation caused by surface rippling generates an oscillatory ponderomotive force, directly modulating transverse electron density at a faster growth rate than that of ions and eventually enhancing instability growth. Our results show that when surface deformation becomes obvious, electron surface oscillation at 2ω0 (where ω0 is the laser frequency) is excited simultaneously, which can be seen as a signature of this mechanism.